2004
DOI: 10.1089/zeb.2004.1.287
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Map ofXiphophorusFishes Represented by 24 Multipoint Linkage Groups

Abstract: Hybrids between distinct Xiphophorus species have been utilized for over 70 years to study melanoma and other neoplasms that can develop spontaneously in hybrid offspring. Genetic linkage mapping has proven to be important in delineating genomic areas that harbor oncogenes and tumor suppressors. Within this report, two parallel backcrosses have been utilized to generate a genetic linkage map for Xiphophorus fishes. Isozyme/allozyme, RFLP and PCR-based mapping techniques, including AP-PCR/RAPDs and microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
0
22
1
Order By: Relevance
“…An androgenetic haploid linkage map of Danio was estimated at 1010 cM, but a gynogenetic map at 2583 cM (Singer et al 2002). By contrast, Xiphophorus does not show any sex-specific differences in recombination rates (Kazianis et al 2004a;Walter et al 2004). Most previous studies have not revealed consistent differences in recombination rates between guppy sexes (Khoo et al 2003;Watanabe et al 2004;Brummell et al 2006), although one report suggested a greater length in males (Shen et al 2007).…”
Section: Introductionmentioning
confidence: 77%
“…An androgenetic haploid linkage map of Danio was estimated at 1010 cM, but a gynogenetic map at 2583 cM (Singer et al 2002). By contrast, Xiphophorus does not show any sex-specific differences in recombination rates (Kazianis et al 2004a;Walter et al 2004). Most previous studies have not revealed consistent differences in recombination rates between guppy sexes (Khoo et al 2003;Watanabe et al 2004;Brummell et al 2006), although one report suggested a greater length in males (Shen et al 2007).…”
Section: Introductionmentioning
confidence: 77%
“…Xiphophorus itself is a well-established model for cancer research, since melanoma can be induced in these fishes through interspecific crossing [Meierjohann et al, 2004;Meierjohann and Schartl, 2006]. Genetic maps are available for Xiphophorus [Kazianis et al, 2004], making the identification and isolation of genes for various traits, including sex determination and differentiation, possible.…”
Section: The Platyfish Xiphophorus Maculatus and Other Poeciliidsmentioning
confidence: 99%
“…Several molecular markers are available for the sex chromosomes of the platyfish, and the sex-determining region has been mapped to linkage group 24 [Kazianis et al, 2004;Woolcock et al, 2006]. Importantly, the Xiphophorus melanoma receptor tyrosine kinase oncogene Xmrk, which corresponds to the tumor locus Tu , is closely linked to the sex-determining locus [Wittbrodt et al, 1989].…”
Section: The Platyfish Xiphophorus Maculatus and Other Poeciliidsmentioning
confidence: 99%
“…3,4 The ease with which fish that spontaneously develop malignant tumors can be produced has resulted in a wealth of genetic information now available, including genetic linkage maps. [15][16][17] Crossing designs producing offspring with malignant tumors in Xiphophorus hybrids were first explored more than 70 years ago. 18,19 The most famous crossing design, termed the "Gordon-Kosswig" cross after its creators, uses a Xiphophorus maculatus female mated to an X. helleri male, backcrossed to X. helleri.…”
Section: Xiphophorus As a Model Study Systemmentioning
confidence: 99%
“…The resulting backcross hybrid offspring segregate alleles at two unlinked loci such that one quarter develops melanoma. 3,16,20 One locus involved in this melanoma is normally involved in pigment cell production; the other is a tumour suppressor locus. * 16…”
Section: Xiphophorus As a Model Study Systemmentioning
confidence: 99%